KNOWLEDGE AND ATTITUDES OF BACCALAUREATE SOCIAL WORK STUDENTS ABOUT INTERPROFESSIONAL COLLABORATION IN CANADA - Azulai, Anna; Vipond, Celina (Canadian Social Work Review / Revue canadienne de service social, 2023)
Although interprofessional collaboration is a common expectation in social work employment, interprofessional education has not been a robust feature of baccalaureate social work preparation in Canada. There is also a dearth of research on the topic. These gaps are problematic because social workers with baccalaureate degrees are often employed in interprofessional teams in various health care settings in Canada. To address this gap in knowledge, this mixed methods study explores attitudes toward interprofessional collaboration of social work students in a Canadian undergraduate university. Also, the study evaluates the students’ knowledge acquisition of interprofessional competencies after a single interprofessional education event. Findings indicate a positive change in students’ attitudes and enhanced knowledge of the interprofessional care competencies. The study contributes to the limited body of research on interprofessional education of baccalaureate-level social work students in Canada. It also shows the power of a single interprofessional experiential event in benefiting professional education of future social work professionals.